2019
DOI: 10.1002/jctb.6194
|View full text |Cite
|
Sign up to set email alerts
|

Biochar‐mediated oxidation of phenol by persulfate activated with zero‐valent iron

Abstract: BACKGROUND Biochar, a by‐product of the pyrolysis of biomass, was used to investigate activation of persulfate in the presence of zero‐valent iron, Fe(0), for the purposes of phenol degradation. Relevant factors of pH, persulfate concentration, and type of black carbon (biochar, activated carbon, and graphite) were examined. RESULTS Maximal removal of phenol was obtained at an initial pH of 2 in Fe(0)–biochar–persulfate systems. At a pH of 7, 89% of the phenol was degraded, with 2.60 mmol L−1 of persulfate, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…41 Previous studies showed that the presence of Mn 3+ /Mn 4+ in MnO 2 and persistent free radicals (as a form of surface functional groups) were responsible for enhancing phenol oxidation by persulfate in the presence of MnO 2 and biochar, respectively. 16,41,64…”
Section: Oxidation Of Phenol By Persulfate With Nano-mno 2biochar Com...mentioning
confidence: 99%
“…41 Previous studies showed that the presence of Mn 3+ /Mn 4+ in MnO 2 and persistent free radicals (as a form of surface functional groups) were responsible for enhancing phenol oxidation by persulfate in the presence of MnO 2 and biochar, respectively. 16,41,64…”
Section: Oxidation Of Phenol By Persulfate With Nano-mno 2biochar Com...mentioning
confidence: 99%
“…•− can be generated in different ways; from the activation of persulfate by short UV (UV-C) light, thermally, via power ultrasound and microwave radiation, as well as transition metals and metal oxides. Zero-valent iron activation with peroxydisulfate on the other hand is a relatively cost-effective, efficient and environmentally friendly method and thus has received considerable attention for the removal of emerging contaminants and pollutants (Kusic et al 2011;Xiong et al 2014;Nguyen and Oh 2019). Zero-valent iron activation not only serves as a slow-releasing source of Fe but also provides a heterogeneous medium for peroxydisulfate activation via direct electron transfer.…”
Section: Zero-valent Iron-activated Persulfate Oxidation Of Alkylphen...mentioning
confidence: 99%
“…The surface structural properties and functional groups were identified by Fourier transform infrared (FTIR) spectra. The biochar is used as an adsorbent material for treating wastewater as a high surface area and hole-like structure can perform an essential role in surface adhesion of methyl orange and chromium (Nguyen and Oh, 2019). The IR spectra of the poultry manure-derived biochar are shown in Figure 4.…”
Section: Characterizationmentioning
confidence: 99%